1981
DOI: 10.1007/bf00234544
|View full text |Cite
|
Sign up to set email alerts
|

Changes in oxytocin content in the magnocellular neurons of the rat hypothalamus following water deprivation or estrogen treatment

Abstract: The effect of water deprivation or estrogen treatment on the oxytocin content of rat hypothalamic cells was examined using a quantitative immunohistological technique. Oxytocin-containing cells were visualized using the immunoperoxidase technique of Sternberg and a primary antiserum directed against oxytocin. The optical density of the darkest 3.2 micrometer diameter spot in the cytoplasm of a cell was used as a measure of the oxytocin content of that cell. Water deprivation produced a significant decrease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

1981
1981
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 11 publications
0
14
1
Order By: Relevance
“…There are some discre pancies, however, between our results and those seen by Rhodes et al [40] using immunohistological techniques. They found relatively less staining of the OT-containing cells in the ACN of day 22 pregnant and day 5 nursing ani mals than in OVXed animals.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…There are some discre pancies, however, between our results and those seen by Rhodes et al [40] using immunohistological techniques. They found relatively less staining of the OT-containing cells in the ACN of day 22 pregnant and day 5 nursing ani mals than in OVXed animals.…”
Section: Discussioncontrasting
confidence: 57%
“…Unfortunately. Rhodes et al [40] did not test animals earlier in pregnancy when we found significantly elevated OT levels. That immunohisto chemical techniques found less staining of OT-containing cells from pregnant than OVXed animals while immunore active levels of extracts from punches of the ACN found about the same or slightly more OT might indicate that the RIA technique is detecting more OT during pregnancy.…”
Section: Discussionmentioning
confidence: 96%
“…[49][50][51][52][53][54][55][56][57] Furthermore, recent studies have provided evidence of a gonadal steroid modulatory role on OT synthesis in the hypothalamus and of gonadal steroid induction of OT receptors in the anterior pituitary (see chapters by Brooks, Johnson, Pfaff et al, and Schumacher et al). 13 An important consideration is whether or not the OT secretory activity in the median eminence alters with the dynamic changes of the plasma level of gonadal steroids during the reproductive cycle.…”
Section: Plasma Oxytocin Release During Reproductive Cyclementioning
confidence: 99%
“…Oxytocinergic cells in the LSN showed increased immunostaining after short-term treatment with silastic implants of estrogen (6), but decreased immunostaining after lower levels of estrogen in ovariectomized (OVX) rats (7). Longer term estrogen treatment (at least a month) also resulted in decreased OXT immunostaining in the anterior commissural nucleus (ACN), a collection of oxytocinergic cells caudal to the LSN and rostral to the PVN (6,8).…”
Section: Introductionmentioning
confidence: 99%
“…Oxytocinergic cells in the LSN showed increased immunostaining after short-term treatment with silastic implants of estrogen (6), but decreased immunostaining after lower levels of estrogen in ovariectomized (OVX) rats (7). Longer term estrogen treatment (at least a month) also resulted in decreased OXT immunostaining in the anterior commissural nucleus (ACN), a collection of oxytocinergic cells caudal to the LSN and rostral to the PVN (6,8).Although estrogen has been shown to influence a number of OXT physiological functions, and is required for the reproductive behavioral effects of OXT (9-13), the effects of estrogen on OXT gene expression have been elusive. Van To1 el al.…”
mentioning
confidence: 99%